(untitled) (The Journal of Geography Education in Africa, 2021)
Teacher migration is a phenomenon that gained international momentum more than eighteen years ago. South Africa was one of the developing countries within the Commonwealth which were greatly affected by the loss of homegrown skills in respect to teacher emigration to the United Kingdom. In the past ten years, however, South Africa has attracted teachers from neighbouring countries. Whilst there have been some studies on migrant teachers in South Africa, research on migrant teachers in primary schools is a neglected area. This paper reports on some of the findings of a qualitative teacher immigration study undertaken in Johannesburg which focussed on primary school teachers. The paper explores the economic, political, and social reasons for migrant teachers teaching in Johannesburg. The push and pull theory of the seminal scholar, Lee (1966) and Bett’s (2010) insights into survival migration and chain migration provide the theoretical dimensions for this paper. Primary school teachers from both public and private schools participated in this research and data was generated through interviews and focus group discussions. Migrant teachers select Johannesburg, South Africa as a survival strategy for a range of economic, political and social reasons. Primary schools in Johannesburg have been overcoming their teacher shortages with this influx of migrant teachers, benefitting from this brain gain.